Analysis of the Suitability of Clove Plants in Pelabuhan Ratu Sub-District - Christian, Yoga Alfa; Manessa, Masita Dwi Mandini; Setiadi, Hafid (Universitas Pendidikan Ganesha, 2024)
Indonesia is the largest clove-producing country in the world, this is because cloves are native plants from Indonesia which are also supported by natural conditions, climate, and topography. In Sukabumi Regency, cloves are the main production center in West Java. This study uses the scoring method by overlaying the data used. The data used in this study are rainfall data, soil type data, slope data, and altitude data. The results of this study found that the area for the